The D826V point mutation in IREB2 induces lipogenesis in adipose tissues - Lv, Yibing; Wu, Chunyu; Xiao, Junyi; Yang, Wenke; Wang, Chenyang; Wang, Jinming; Huang, Jianmei; Guo, Zhenglong; Liao, Shixiu (Frontiers in Cell and Developmental Biology, 2026)
BackgroundIREB2 is an RNA-binding protein that modulates cellular iron uptake and storage by regulating ferritin expression. Mutations in the IREB2 gene have been shown to induce degradation of the IREB2 protein, resulting in the upregulation of FTH1 protein expression, which contributes to iron storage. This study investigates the potential mechanism of the Ireb2D826V/D826V mutation on lipid biosynthesis for the first time.ResultsIn this study, it was discovered for the first time that Ireb2D826V/D826V mice exhibited increased body weight, hypertrophic adipocytes, iron and lipid accumulation. RNA-sequencing analysis suggests that the Ireb2D826V/D826V mutation potentially activates pathways involved in fatty acid and triglyceride biosynthesis. This activation is evidenced by the upregulation of lipid biosynthetic genes, including Fasn, Acaca, Acly, Fgfr4, and Egr1, along with their corresponding protein expressions in Ireb2D826V/D826V mice. These molecular changes occur alongside the degradation of IREB2, an increase in FTH1 expression and iron accumulation in tissues. Metabolomic analysis confirmed that the Ireb2D826V/D826V mutation indeed elevated the levels of certain fatty acids and triglyceride components in epWAT. Moreover, in vitro experiments utilizing adipocytes confirmed that the Ireb2D826V/D826V mutation augmented fatty acid and triglyceride biosynthesis, as well as the expression of associated proteins, contingent upon iron accumulation.ConclusionThe Ireb2D826V/D826V mutation is linked to the degradation of IREB2, increased expression of FTH1, and iron accumulation. These molecular alterations are associated with elevated protein levels of ACACA, ACLY, FASN, EGR1, and FGFR4, which correlate with enhanced lipid biosynthesis and subsequent weight gain. This study elucidates a link between dysregulated iron storage, mediated via the IREB2-FTH1 axis, and the upregulation of key lipogenic genes, resulting in enhanced lipid biosynthesis. These findings underscore a potential relationship between iron metabolism and obesity, suggesting that iron homeostasis could serve as a valuable target for further mechanistic investigation and therapeutic development in the context of obesity.